2017
DOI: 10.1186/s13068-017-0993-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide produced from Bacillus sp. W112 improves the hydrolysis of lignocellulose by specifically reducing non-productive binding of cellulases with and without CBMs

Abstract: BackgroundSurfactants have attracted increasing interest for their capability to improve the enzymatic hydrolysis of lignocellulosic biomass. Compared to chemical surfactants, biosurfactants have a broader prospect for industrial applications because they are more environmentally friendly and more effective in some researches. Commercial cellulase preparations are mainly composed of endoglucanases (EGs) and cellobiohydrolases (CBHs) that possess carbohydrate-binding modules (CBMs). However, the effects of lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Biosurfactants are also applicable to improve the degradation of complex biomass in so-called biorefinery processes to exploit alternative industrial resources. Here, their supplementation may enhance enzymatic lignocellulose degradation efficiency, probably by the improvement of substrate binding of the applied cellulases [212]. Another study reported increased hydrogen production from organic solid waste through surfactin and saponin supplementation [213].…”
Section: Applications Of Biosurfactantsmentioning
confidence: 99%
“…Biosurfactants are also applicable to improve the degradation of complex biomass in so-called biorefinery processes to exploit alternative industrial resources. Here, their supplementation may enhance enzymatic lignocellulose degradation efficiency, probably by the improvement of substrate binding of the applied cellulases [212]. Another study reported increased hydrogen production from organic solid waste through surfactin and saponin supplementation [213].…”
Section: Applications Of Biosurfactantsmentioning
confidence: 99%
“…For example, rhamnolipid biosurfactant produced by P. aeruginosa BWL1001 was used to accelerate the biodecolorization efficiency of azo dyes (Liu, You, et al, 2017); lipopeptide biosurfactant produced from Bacillus sp. W112 was applied to improve the hydrolysis of lignocellulose by specifically reducing nonproductive binding of cellulases (Liu, Zhu, et al, 2017); sophorolipid biosurfactant secreted from Rhodotorula babjevae YS3 exhibits antifungal activities against plant and human pathogens (Sen et al, 2017); biosurfactants produced by Bacillus licheniformis L20 and Achromobacter sp. A‐8 have been used to enhance oil recovery and bioremediation (Deng et al, 2020; Liu et al, 2021); biosurfactants secreted from P. aeruginosa SS14 and Bacillus tequilensis SDS21 showed anti‐biofilm activity (Borah et al, 2019; Singh & Sharma, 2020); biosurfactants produced by Bacillus nealsonii S2MT, B. subtilis LAMI005 and Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FTIR) was performed to analyze the functional groups in BS‐51 (Liu, Zhu, et al, 2017). The lyophilized BS‐51 sample was milled and compressed with pure KBr powder, and the spectrum of BS‐51 was recorded using a Fourier transform infrared spectroscopy (Bruker Tensor 27) in a wave range from 600 to 4000 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the CDs of different GH5 family members display different affinities for lignin, with binding being driven by electrostatic interactions or hydrogen bonding depending on the enzyme in question [10, 12, 19]. Many efforts have been devoted to the prevention of non-productive adsorption in enzymatic hydrolysis, such as changing pretreatment conditions [20, 21] or blocking the exposed lignin surface using bovine serum albumin (BSA) and additives [2224]. A promising alternative approach would be engineering or discovering natural cellulases with low lignin-binding propensities, relying on a full understanding of enzyme–lignin interactions [17].…”
Section: Introductionmentioning
confidence: 99%